The impact of social support on career decision-making difficulties: The serial mediating roles of career decision-making self-efficacy and job search clarity, and moderation by proactive personality - Rong Chen; Qin Zhang; Yunfei Cao (PLoS ONE, 2026)
Career decision-making difficulties are a common challenge for college students, which can hinder their transition from education to employment. Based on the Social Cognitive Model of Career Self-Management, this study explored how social support was related to career decision-making difficulties. A total of 991 vocational college students participated in this cross-sectional quantitative study. Social support was measured through the Perceived Social Support Scale, career decision-making self-efficacy with the Career Decision-Making Self-Efficacy Questionnaire, job search clarity via the Job Search Clarity Questionnaire, career decision-making difficulties using the Career Decision-Making Difficulties Questionnaire, and proactive personality by the Proactive Personality Scale. The results showed that: Job search clarity partially mediates the relationship between social support and career decision-making difficulties. The indirect effect was significant, β = −0.08, p < 0.001, accounted for 20% of the total effect. In addition, career decision-making self-efficacy and job search clarity jointly serve as serial mediators in the link between social support and career decision-making difficulties. The serial indirect effect was significant, β = −0.12, p < 0.001, accounting for 30% of the total effect, indicating that higher social support sequentially enhances career decision-making self-efficacy and job search clarity, which in turn reduces career decision-making difficulties. Furthermore, proactive personality moderates the mediating role of job search clarity, particularly in the second stage of the mediation. Specifically, the effect of job search clarity on career decision-making difficulties became more pronounced as proactive personality increased (β = −0.04, p < 0.001). These findings extend the social cognitive model of career self-management by demonstrating the sequential mediating roles of career decision-making self-efficacy and job search clarity, and the moderating role of proactive personality, in the link between social support and reduced career decision-making difficulties. Practically, they highlight the importance of designing career interventions for vocational college students that simultaneously strengthen social support networks, enhance self-efficacy, and build job search clarity, with particular attention to students with lower proactive personality who may benefit most from such clarity-building activities.